New Contradictions of Economic Thought in the Works of Jean Charles Léonard Simonde de Sismondi – Demonstration of the Dangers of Relying on Sismondi for Public Policymaking - Pirot, Florent; Mezhennaya, Maria; Lavin, Claire (European Journal of Applied Sciences, 2025)
This article provides an elaborated view on why Sismondist theories are incompatible with logic. Sismondist ideas present several contradictions that make Sismondist views incompatible with economic policy. Praxeology, inspired by Henri Fayol’s concepts of the private company organization, leads to the economic demonstration of the impossibility of Sismondism as an ideology. Technology is also shown to be for instance vastly superior to Sismondist antitechnologism up to the issues most at heart of Sismondi : military self-defense and agriculture, including in the traditional sharecropping areas that have inspired Sismondi. An alternative, Democratic-Republican view based on anarchocapitalist principles that covers military self-defense of the society as well as economic organization and social welfare is presented at the end.